The Polemic of Female Circumcision in Garut West Java Indonesia: Clash of Culture and Regional Policy - Atu Setiati; Aziz Muslim; Farhana Sabri (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Female circumcision remains a social issue in Muslim society, along with the rise of gender-based violence cases in Indonesia. It has became rather a polemic after regional policy on that matter was issued inconsistently. This study aimed to determine the polemic of female circumcision in Garut Regency based on cultural and regional policy analysis. The study utilized qualitative method with an ethnographic approach. The data taken were based on primary data and secondary data. Data collection techniques used were interviews and literature that supports the research. The results obtained in this study are that the polemic about female circumcision occurs because of differences in views based on fatwa so that society constructs female circumcision subjectively. Differences in the belief in the concept of female circumcision, which has become a culture in society, and the different techniques or processes for implementing female circumcision have resulted in the development of perceptions of female circumcision. The inconsistency of the policies of the Minister of Health Regulations makes the community have a bias towards pros and cons by the paradigm of religious leaders, parents, gender activists, and health workers.